Klasifikasi Status Penerima Bantuan Program Keluarga Harapan di Provinsi NTB Menggunakan Metode Regresi Probit - Harsyiah, Lisa; Widya Baskara, Zulhan; Eka Putri, Dina; Jurniati, Jurniati; Zulhan Widya Baskara (FKIP Universitas Mataram, 2025)
The Indonesian government's effort to accelerate the achievement of comprehensive social welfare involves adopting strategic policies in the form of distributing social assistance to economically vulnerable communities. One concrete example of this policy is the Family Hope Program (Program Keluarga Harapan/PKH). However, its implementation in the field still faces challenges, particularly in the form of unequal distribution, which has the potential to hinder the program’s effectiveness. To address this issue, a rigorous verification system is required to ensure that prospective beneficiaries truly meet the official criteria set by the government. Therefore, classifying households eligible for PKH is a crucial step. The probit regression approach is employed as a method to analyze and determine the household eligibility status. This method yields an accuracy rate of 76.25%, which is considered valid and reliable based on the Press’s Q statistic